2019
DOI: 10.1530/erc-19-0042
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic strategies to induce ERα in luminal breast cancer to enhance tamoxifen efficacy

Abstract: Breast cancer is the most prevalent malignancy and second leading cause of death in women worldwide, with hormone receptor-positive luminal breast cancers being the most widespread subtype. While these tumors are generally amenable to endocrine therapy, cellular heterogeneity and acquired ability of tumor cells to undergo cell state switching makes these populations difficult to be fully targeted and eradicated through conventional methods. We have leveraged a quality-by-design (QbD) approach that integrates b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…To establish a ESR1-mediated miRNA-mRNA regulatory network in ERα positive breast cancer, we searched for the potential datasets in the Gene Expression Omnibus database (http://www.ncbi.nlm.nih.gov/geo/). Only datasets met the following criteria were first included: (1) these data should be derived from tumor tissues of patients with ERα positive breast cancer; (2) included datasets should contain miRNA and mRNA transcriptome data. Then, the abstracts and corresponding information of the datasets of interest were further evaluated.…”
Section: Microarray Expression Profilingmentioning
confidence: 99%
See 1 more Smart Citation
“…To establish a ESR1-mediated miRNA-mRNA regulatory network in ERα positive breast cancer, we searched for the potential datasets in the Gene Expression Omnibus database (http://www.ncbi.nlm.nih.gov/geo/). Only datasets met the following criteria were first included: (1) these data should be derived from tumor tissues of patients with ERα positive breast cancer; (2) included datasets should contain miRNA and mRNA transcriptome data. Then, the abstracts and corresponding information of the datasets of interest were further evaluated.…”
Section: Microarray Expression Profilingmentioning
confidence: 99%
“…Breast cancer is the most common type of cancer and the second prevalent cause of cancer-associated deaths in women worldwide (1). In the United States, an estimate of 252,710 women will be diagnosed with breast cancer every year, with approximately 41,070 breast cancer-associated deaths (2). As the complexity of breast cancer, there are more than 20 various histological subtypes and at least four distinct molecular subtypes (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Genome-based profiling analysis showed that breast cancer can be classified into four molecular subtypes: luminal A, luminal B, HER2 and basal-like [2]. Among the subtypes, luminal A and B account for approximately two-thirds of cases and could benefit from endocrine therapy [3]. Selective estrogen receptor modulators (SERMs) have become the standard treatment for ER alpha-positive patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is initiated when healthy cells grow beyond control to form a mass known as a tumor. Breast cancer, which affects both humans and other mammals, can take place in the inner lining of milk ducts (ductal carcinomas), or the lobules of the breast (lobular carcinomas) [1]. The most prevalent type of breast cancer is the hormone receptor-positive luminal breast cancer.…”
Section: Introductionmentioning
confidence: 99%